(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Asthma is a prevalent chronic respiratory disease in childhood globally. Achieving and maintaining asthma control is crucial for improving quality of life and reducing healthcare burdens. The Childhood Asthma Control Test (C-ACT) is a validated tool for assessing asthma control in children aged 4-12 years. This study aimed to assess the level of asthma control using the C-ACT and to identify associated socio-demographic and clinical factors among children with asthma. A cross-sectional study was conducted between October 2022 and March 2024 at major pediatric outpatient clinics at Al-Kadhimiya Teaching Hospital. Children aged 4-12 years with a physician diagnosis of asthma for at least 6 months were included. Data were collected using a structured questionnaire covering socio-demographics, clinical characteristics (asthma severity, duration, treatment, adherence, triggers, and exacerbation history), as well as the validated Arabic version of the C-ACT. Asthma control was categorized based on the C-ACT score (≤19 = uncontrolled, >19 = controlled). Statistical analysis included descriptive statistics, chi-square tests, t-tests, and multivariate logistic regression to identify predictors of uncontrolled asthma. A total of 280 children, mean age 7.2 ± 2.1 years (58% male), participated. The mean C-ACT score was 17.9 ± 4.5. Overall, 168 children (60%) had uncontrolled asthma (C-ACT score ≤19). Multivariate logistic regression identified moderate/severe asthma classification (OR=3.8), poor medication adherence (OR=3.1), and exposure to household tobacco smoke (OR=2.2) as significant independent predictors of uncontrolled asthma. A high proportion of children with asthma in Baghdad suffer from uncontrolled disease according to the C-ACT. Factors such as disease severity, poor medication adherence, and environmental exposures are key contributors.